Faktor yang Berhubungan dengan Dermatitis Kontak pada Pekerja Udang di PT. Sultratuna Samudra Kendari - Arum Dian Pratiwi Arum (Universitas Widya Gama Mahakam Samarinda, 2020)
Background: PT. Sultratuna Samudra Kendari is a company whose one unit of activity is exporting shrimp. In the shrimp, there are several ingredients that can be irritant to the skin. Besides that, in the washing of shrimp, this company uses chlorine, which also affects the skin if it hits the skin.. Contact dermatitis can be caused by poor personal hygiene, prolonged contact with irritants, use of Personal Protective Equipment (PPE), and a history of skin allergies. Objectives: The purpose of this study was to determine the related factors including personal hygiene, contact duration, use of Personal Protective Equipment (PPE), and a history of skin allergies with the incidence of contact dermatitis in shrimp workers at PT. Sultratuna Samudra Kendari in 2018. Research Methods: This type of research is analytic observational with cross-sectional study approach. This research was conducted in the working area of PT. Sultana Samudra Kendari. The population in this study were all shrimp workers of PT. Sultratuna Samudra Kendari, amounting to 128 people with a sample of 44 respondents using accidental sampling technique.. Results: The results showed that, based on the diagnosis of doctors suffering from contact dermatitis were 28 respondents (63.6%) and did not suffer from contact dermatitis were 16 respondents (36.4%), there was a relationship between personal hygiene (p-value = 0.003) , contact duration (p-value = 0.041), use of Personal Protective Equipment (PPE) (p-value = 0.002), and history of skin allergy (p-value = 0.002) with the incidence of contact dermatitis in shrimp workers at PT. Sultratuna Samudra Kendari. Conclusion: Factors associated with contact dermatitis in PT. Sultratuna Samudra Kendari is personal hygiene, contact duration, use of PPE, and a history of skin allergies. Keywords: Contact Dermatitis, Shrimp